READING OF/IN FRICTION IN THE TRAJECTORY OF HELOÍSA BUARQUE DE HOLLANDA - Cinara Antunes Ferreira (Revista Brasileira de Literatura Comparada, 2022)
This essay presents a reading of the trajectory of the Brazilian researcher Heloísa Buarque de Hollanda through her works, among which are 26 poetas hoje (and its reeditions), Explosão feminista e 29 poetas hoje. We aim to show how the author performs epistemological shifts from a counter-narrative, which materializes in projects such as Universidade das Quebradas, the anticonferences, the texts that make her place of speech explicit, the anthology of marginal poetry, occupation-books, the anthology of women in tune with feminism, among other cultural intervention proposals that make Heloísa an unique intelectual in the scenario of Brazilian and Latin American literary criticism.